Kapasitas UPT Samsat Pekanbaru Kota Dalam Meningkatkan Kualitas Pelayanan Publik - Nesya Hutari (UIR Press, 2023)
This study aims to find out what capacities are needed by UPT SAMSAT Pekanbaru Kota in improving the quality of public services at UPT SAMSAT Pekanbaru Kota, especially in the reception and billing section. The type of data used in this study is Primary Data either through conscious or unconscious interviews with UPT SAMSAT staff and taxpayers (WP). In addition, researchers also conducted direct observations for approximately 2 months. Then Secondary Data is data obtained from other sources that have been written both in the form of written documents and available readings. In improving the quality of service, there are several capacities needed as basic indicators that play a major role in the sustainability of existing activities at UPT SAMSAT Pekanbaru City. Managed capacity, namely, resources which are an entity consisting of humans, methods/methods, machines, markets, money and materials. All of them refer to the discussion of facilities, human capabilities, and work systems in a group. With the appropriateness of observations, this research can measure capacity by using 6 aspects of performance appraisal of public service delivery units in accordance with Ministerial Regulation no. 17/2017, namely Service Policy, Professionalism of HR Operators, Public Service Infrastructure, Public Service Information Systems, Consultation and Complaints, Service Innovation. Based on the results of this study, the capacity level of the UPT SAMSAT Pekanbaru City Office is still not maximized. This requires capacity building, especially in terms of Human Resources (HR) and Infrastructure. And collectively, the government should be observant about which capacities need to be improved and the methods must also be precise and must be firm if there are deviations from the existing rules. Only then can this capacity become an asset that can be utilized as the goal was established to achieve community service satisfaction and at the same time it can change the view or bad image of government services in the eyes of the community.